Perception among Muslims in Malaysia towards in Malaysia towards dental procedures during the fasting month - Said, Abdul Hadi; Mohd, Farah Natashah (2018)
Albarakati (2009) reported that there is reduced in dental attendance during fasting month. Most authors postulated this, because Muslim patients may perceive dental procedures during Ramadhan will nullify their fast. (Shaeesta et al., 2015,Darwish., 2005, Raja et al., 2000) However, to date, there is no study conducted to assess Muslims’ perception towards dental procedures in Ramadhan. Therefore, this research is to assess the perception towards dental procedures in Ramadhan among Muslim adults. This is important to understand their perception and to provide a better dental treatment plan during fasting month for Muslim patients.